Bentuk-Bentuk Penyimpangan dalam Novel Kiat Sukses Hancur Lebur Karya Martin Suryajaya: Kajian Stilistika - Norma Atika Sari (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
This study focused on the analysis of irregularities featured form in the novel Kiat Sukses Hancur Lebur by Martin Suryajaya. The research variables were forms of lexical, grammatical, paragraph, discourse, plot, and forms of narrative delivery. This research was a qualitative descriptive study and data collection was conducted by reading and note taking techniques. The results found that many deviations such as selection of odd words, the formation of incoherent sentences and paragraphs, the discourse that presents a critique of capitalism and postmodernism through symbols, as well as the emergence of unusual forms of novel structures namely footnotes, charts, diagrams, schematics, paintings, drawings, line types, pictures, photographs, tables, balance sheets, formulas, maps and bibliography. These deviations show the author’s unique style and novelty in the form of aesthetic absurdity in the treasury of contemporary Indonesian literature.